PENERAPAN KETERAMPILAN BERPIKIR KRITIS - Jasiah, Jasiah (Jurnal Studi Agama dan Masyarakat, 2014)
Critical Thinking Skills is an activity or a process of analyzing , explaining and developing or selecting ideas , includes categorizing , comparing and contracting ( contrasting ) , examine arguments and assumptions , completing and evaluating the conclusions of induction and deduction , set priorities and make choices. There are three terms related to thinking skills , which is actually quite different ; ie higher-level thinking (high level thinking) , think complex (complex thinking) , and critical thinking (critical thinking). Thinking skills is actually a skill that can be learned and taught , both at school and through independent study. Noteworthy in the teaching of thinking skills is that skills must be done through exercise that is appropriate to the stage of cognitive development of learners.